Concurrent driver mutations/rearrangements in non-small-cell lung cancer. Issue 2 (March 2017) - Tabchi, Samer; Kourie, Hampig R.; Klastersky, Jean
Abstract : Purpose of review: The concept of mutually exclusive oncogenic driver alterations has prevailed over the past decade, but recent reports have stressed the possible occurrence of dual-positive non-small-cell lung cancer (NSCLC) and even triple-positive disease for these oncogenes. This entity presents novel prognostic and therapeutic challenges. The present review highlights the available data in an effort to clarify the clinical and pathological significance of coexisting mutations as well as the subsequent therapeutic consequences. Recent findings: Patients with a known driver oncogene can be successfully treated with the appropriate tyrosine kinase inhibitor, which will provide them with significant responses and lesser toxicities compared with cytotoxic therapy. Unfortunately, most patients will eventually progress. Although some resistance mechanisms have been identified, others remain to be determined but the emergence of secondary oncogenes could be part of the answer. Summary: Approximately 20–25% of NSCLC harbor treatable driver mutations/rearrangements; epidermal growth factor receptor mutation, anaplastic lymphoma kinase and ROS-1 gene rearrangements are the main alterations for which a Food and Drug Administration-approved tyrosine kinase inhibitor can be used. Because of recent technological advances, high sensitivity assays with a broad range of genomic targets have become more easily accessible in clinical practice, which has led to an increased detection of coexisting driver alterations in patients with advanced NSCLC. The prognostic/predictive and therapeutic implications of this novel entity are still unsettled for the time being. Randomized trials specifically designed to address this subset of patients will soon be necessary to help determine the optimal therapeutic agent to administer.